One pot selective synthesis of water and organic soluble carbon dots with green fluorescence emission1. Issue 15 (25th February 2015) - Zheng, Baozhan; Liu, Tao; Paau, Man Chin; Wang, Meina; Liu, Yang; Liu, Lizhen; Wu, Chuanfang; Du, Juan; Xiao, Dan; Choi, Martin M. F.
<x xml:space="preserve">Abstract</x> This work reports a simple and energy-saving strategy for selective synthesis of water-soluble and organic-soluble carbon dots at room temperature.